Mercados de energia e eficiência alocativa em um contexto de transiç\~ao energética - Rafael Cancella Morais; Bruno Scola Lopes da Cunha; Amaro Olimpio Pereira Júnior; Maria Bernadete Gomes Pereira Sarmiento Gutierrez; Mário Jorge Mendonça (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– This study has as main objective to investigate if the energy markets liberalisation, in particular natural gas and electricity, contribute to the energetic transition, led by climate change mitigation policies. More specifically, this study attempts to classify the efficiency degree associated with the energetic transition of countries, taking into account the development state of the natural gas and electricity sectors. A data envelopment analysis is undertaken, more specifically using a Slack Based Measure model (Tone, 2001). This optimisation model compares decision takers units selected by pre-determined variables, which in our case are indicators of market liberalisation and energetic transition in the natural gas and electricity markets. The optimisation process will define an efficiency frontier, capable of classifying countries according to their relative efficiency. These results are presented and analysed with the objective of suggesting improvements in the regulatory framework and in the public ownership so that to improve the energy sector performance of the countries classified as lower efficiency performers relatively.
Keywords: O12; O19; 330; competition; energetic transition; regulation; DEA slack based measure; efficiency